PENERAPAN QANUN ZAKAT NOMOR 10 TENTANG KEPATUHAN PEMBAYARAN ZAKAT PERDAGANGAN DI KALANGAN PEDAGANG KELONTONG DI KABUPATEN PIDIE JAYA - Hafsah, Ansari Yamamah, Munawwar (UIN SU, 2018)
Zakat on business is a type of zakat that is issued from the results of business effort carried out by a Muslim. Based on the Quranic and hadith arguments, the profits obtained by traders who have reached the nishab are obliged to be charged zakat. The purpose of this study is to see how the application of qanun number 10 concerning zakat which includes trade zakat. In this study encompasses issues related to the knowledge of traders on the zakat qanun, then the method of collecting and distributing zakat. Inhibiting and supporting factors both in terms of collecting zakat distribution and the Baitul Mal strategy so that the number 10 qanun can work well. The method used in this study is empirical legal methodology and qualitative analysis, the source of data in this study is divided into secondary data and primary data. Secondary data is used to see the concept of actual zakat trade then primary data is used for the purpose of seeing in terms of its application. From the results of research on the knowledge and understanding of traders about trade zakat, all respondents knew, but they did not issue their zakat to the Baitul Mal. The way zakat is collected is still very weak and slow and the distribution of zakat is in accordance with the collection, Baitul Mal continues to strive and preach so that the payer (muzakki) of zakat continues to increase only the trade zakat that no one pays to the Baitul Mal, the limitation of active Baitul Mal employees hampering the collection and distribution of zakat, but the Baitul Mal step to implement the implementation of qanun number 10 on zakat is still very weak and slow to socialize.